Ambiguous social choice functions - Ghislain-Herman Demeze-Jouatsa (Bielefeld University, Center for Mathematical Economics (IMW), 2021)
Call a mechanism that associates each profile of preferences over candidates to an ambiguous act an Ambiguous Social Function (ASCF). This paper studies the strategy-proofness of ASCFs. We find that an ASCF is unanimous and strategyproof if and only if there exists a nonempty subset of voters, called the set of top voters, such that at each preference profile, the range of the selected act equals the set of top-ranked candidates of top voters. We provide a full characterization of the class of unanimous, strategyproof, and anonymous ASCFs, and provide a large subclass of ASCFs that satisfy the additional property of neutrality.
urn:nbn:de:0070-pub-29603681
Keywords: D71; D72; D81; D82; 330; Social Choice Function; Ambiguity Aversion; Ellsberg Urns; Strategy-proofness; Unanimity; Anonymity; Neutrality